Stealth Mergers and Investment Outcomes - Aggarwal, Rajesh K.; Baxamusa, Mufaddal (Journal of Financial and Quantitative Analysis, 2025)
Abstract “Stealth mergers” are not reported to the government because they fall below the required size threshold. We study stealth mergers involving public targets for which manipulation of transaction sizes is unlikely. These stealth mergers result in less R&D spending, patenting, and capital expenditures, and in lower value patents for both acquiring firms and their competitors relative to non-stealth mergers. Industry concentration increases, and product market competition decreases for stealth acquirers. Stealth acquirers and their competitors earn higher cumulative abnormal returns relative to non-stealth mergers. Our results suggest more government scrutiny is warranted for stealth mergers.